Pengaruh Guncangan Variabel Moneter Terhadap Nilai Tukar Dan Inflasi Di Indonesia - Sintia Pertiwi Agustin; Ali Anis (Universitas Negeri Padang, 2021)
This study aims to determine the effect of monetary variable shocks on the exchange rate and inflation in Indonesia. The variables used to represent monetary conditions are interest rates and the money supply. This study uses secondary data with the type of time series data. The data used in this study is sourced from Bank Indonesia in the form of monthly data from 2015 to 2020. The analytical method used is the Vector Error Correction Model (VECM). The results of this study indicate that in the short term only the money supply has a significant effect on the exchange rate in Indonesia, while interest rates and inflation have no significant effect on the exchange rate in Indonesia. In the long term, the money supply, interest rates, and inflation have a significant effect on the exchange rate in Indonesia. In the short term, only interest rates and exchange rates have a significant effect on inflation in Indonesia, while the money supply has no significant effect on inflation in Indonesia. In the long term, the money supply, interest rates and exchange rates have a significant effect on inflation in Indonesia.